IMPROVING ENERGY EFFICIENCY IN BUILDINGS THROUGH THE USE OF PANORAMIC GLAZING - MATCAN-LISENCO , I. (Art and Design, 2024)
The purpose of this study is to highlight how panoramic windows can significantly enhance energy efficiency in interior spaces. The aim is to identify and discuss the main benefits and disadvantages of these windows, as well as their classification according to the destination of the respective space. Methodology: the study was based on extensive bibliographic research, analyzing various sources such as books, articles and specialized publications in the field of architecture and energy efficiency. The author evaluated and interpreted the data and results obtained, organizing them logically to provide a coherent presentation of the topic. Results. The effective utilization of panoramic windows offers numerous benefits for enhancing energy efficiency indoors, including improved thermal insulation, optimized utilization of natural light, efficient control of solar radiation, and promotion of natural ventilation. Despite associated drawbacks such as thermal losses and maintenance costs, proper classification and climate adaptation can maximize energy efficiency and indoor comfort in buildings. Scientific novelty. The study explores the energy efficiency of buildings through the optimization of panoramic windows across various climatic and cultural contexts, employing advanced technologies in thermal insulation and solar control. Results, derived from exhaustive research and empirical data, underscore the advantages of these windows in enhancing the energy efficiency of buildings. Practical significance. The study highlights the multiple practical advantages of panoramic windows, such as improving thermal insulation and solar control, leading to energy savings and increased indoor comfort. The efficient use of energy through these windows not only reduces CO2 emissions but also protects the environment, promoting responsible resource consumption and contributing to societal progress through ecological innovations.